Moving and exploring the world sensorially: Liv Hanne Haugen’s dance classes in Tromsø - Švandere, Aliki (UiT Norges arktiske universitet, 2024)
This paper is part of a master's thesis project in visual anthropology, which includes also a short ethnographic film “Dance what you are”. The project is based on three months of fieldwork conducted in Tromsø, a city in Northern Norway. It focuses on a group of people who practice a dance which none of them can define or label. The dance does not have a choreography, a specific technique, or (explicitly communicated) rules of the right behavior, and is usually practiced non-verbally and without specific objects used in creation. The research addresses the following questions: why would a person choose to engage in open, minimally structured dance classes, what constitutes this experience and how is it meaningful? Methods for gathering ethnographic material in this study include (a) participant observation with a camera conducted during dance classes and (b) interviews held in separate meetings with people who practice the dance. In this paper, it is argued that open spaces for creative body movement and sensorial exploration, such as the dance classes I researched, create opportunities for connecting to oneself and others corporeally. These connections are formed in a process of embodied active listening and resonating, that is, attentively sharing a space with others. This kind of attentive, present, embodied way of being motivates the dancers to attend the classes. What adds to the meaningfulness of the dance experience is a transformational effect of creative expression and a freedom to explore being in the world in an open and physically intimate manner.